Prognostic value and clinicopathological status of PD-L1 expression and CD8+ TILs in oral squamous cell cancer patients with or without traditional risk factors - Soopanit T. (2023)
Background: Non-smokers, non-drinkers, and non-betel quid chewers (NSNDNBs) with oral squamous cell carcinoma (OSCC) have poor survival outcomes. Tumor microenvironment based on PD-L1/CD8+ T cell infiltrated lymphocyte (TIL) proportion is proposed as a prognostic indicator. Methods: Immunohistochemistry staining was performed on OSCC samples from 64 patients. The PD-L1/CD8+ TILs were scored and stratified into four groups. Disease-free survival (DFS) was analyzed using a Cox regression model. Results: OSCC in NSNDNB patients was associated with female sex, T1-2 classification, and PD-L1 positivity. Low CD8+ TILs correlated with perineural invasion. High CD8+ TILs correlated with improved DFS. PD-L1 positivity was not correlated with DFS. Type IV tumor microenvironment yielded the highest DFS (85%). Conclusion: NSNDNB status relates to PD-L1 expression regardless of CD8+ TILs infiltration. Type IV tumor microenvironment was associated with the best DFS. High CD8+ TILs resulted in better survival, while PD-L1 positivity alone was not correlated to DFS.